Pembuatan Mesin Perontok Padi - Hanun, Siti Afifah Latifah; Riandadari, Dyah (Universitas Negeri Surabaya, 2021)
Indonesia is one of the largest rice producing countries in the world (6,905,612,600 tons with a harvested area of 1,344,552,400 Ha). Rice is a national strategy commodity and is consumed by most of the Indonesian population. Rice consumption continues to grow along with population growth. Therefore, rice production must also increase according to the demand for rice needs. The increase in rice production has generally been successful, but the added value obtained has not been fully enjoyed by farmers, especially the high yield loss. The purpose of this research is to make/build a rice thresher machine with a capacity of 100 kg/hour and to get a value for the production capacity of a rice thresher machine with a 6.5 HP machine. This research uses the Research and Development (R&D) method or experimental-based development research, namely by developing a rice thresher machine (thresher). The thresher design used Solidworks 2014 software with a length of 730 mm, a circumference of 370 mm in diameter and a threshing tooth length of 8 cm. The threshing cylinder is made using a shaft iron material with a thickness of 1 inch, 9 screw threads with a diameter of 9 mm circumference, a strip plate with a thickness of 2 mm iron and concrete iron with a length of 8 cm. The test results of the rice thresher machine produced 63 kg/30 minutes with a 6.5 hp engine with a capacity of 3600 rpm with a gas opening of 3/4 and fuel consumption of 1 liter/half hour.